Phylogenetic analysis of LSU and SSU rDNA group I introns of lichen photobionts associated with the genera Xanthoria and Xanthomendoza (Teloschistaceae, lichenized Ascomycetes). Issue 6 (11th November 2013) - Nyati, Shyam; Bhattacharya, Debashish; Werth, Silke; Honegger, Rosmarie; De, O.
<x xml:space="preserve">Abstract</x> We studied group I introns in sterile cultures of selected groups of lichen photobionts, focusing on Trebouxia species associated with Xanthoria s. lat. (including Xanthomendoza spp.; lichen‐forming ascomycetes). Group I introns were found inserted after position 798 (Escherichia coli numbering) in the large subunit (LSU) rRNA in representatives of the green algal genera Trebouxia and Asterochloris. The 798 intron was found in about 25% of Xanthoria photobionts including several reference strains obtained from algal culture collections. An alignment of LSU‐encoded rDNA intron sequences revealed high similarity of these sequences allowing their phylogenetic analysis. The 798 group I intron phylogeny was largely congruent with a phylogeny of the internal transcribed spacer region, indicating that the insertion of the intron most likely occurred in the common ancestor of the genera Trebouxia and Asterochloris. The intron was vertically inherited in some taxa, but lost in others. The high‐sequence similarity of this intron to one found in Chlorella angustoellipsoidea suggests that the 798 intron was either present in the common ancestor of Trebouxiophyceae, or that its present distribution results from more recent horizontal transfers, followed by vertical inheritance and loss. Analysis of another group I intron shared by these photobionts at small subunit position 1512 supports the hypothesis of repeated lateral transfers of this intron among some taxa, but loss among others. Our data confirm that the history of group I introns is characterized by repeated horizontal transfers, and suggests that some of these introns have ancient origins within Chlorophyta.